Gender, labor, and prime-age adult mortality: evidence from South Africa - Yamauchi, Futoshi; Buthelezi, Thabani; Velia, Myriam (International Food Policy Research Institute, 2006)
This paper assesses the impact of prime-age mortality on human capital formation and labor markets by examining, first, the impact on adolescents, who may leave school in order to enter the labor market, and second, the impact on adult females who, upon the loss of a breadwinner, may decide to seek a job outside of the home.